Gluten contamination of canned and dry grain-free commercial pet foods determined by HPLC-HRMS. Issue 1 (14th December 2020) - Meineri, Giorgia; Candellone, Alessia; Dal Bello, Federica; Gastaldi, Daniela; Medana, Claudio; Peiretti, Pier Giorgio
Abstract: The aim was to determine the absence of gluten in pet food samples marked as 'grain-free' and 'gluten-free' diets, to assess the reliability of manufacturer labelling of such products. A total of 15 diets labelled as grain- or gluten-free and 2 commercial diets containing wheat were sampled. An analytical procedure using high-pressure liquid chromatography coupled with mass spectrometry with high power of resolution was developed and applied to determine specific markers of wheat gluten. The results are expressed as mg of wheat flour type '00' present in 1 g of feed. The quantification limit (LOQ) obtained in the flour for ion m/z 894.5043, z = 2, is 4 mg of flour per gram. In 14 out of the 15 samples from a grain- or gluten-free diet the quantifier ion signal was < LOQ, while in 1 out of the 15 samples 10 mg of flour/g feed were measured. Highlights: Adverse reaction to gluten in dogs have been documented in certain breeds Gluten is tricky to detect and measure in pet food Contamination of gluten in pet food samples marked as 'grain-free' and 'gluten-free' diets An analytical procedure was developed using HPLC coupled with HRMS